Hubungan Dukungan Sosial Terhadap Kualitas Hidup Caregiver Kanker Payudara - Lilia Lopes; Yovita Dwi Setiyowati; Wilhelmus Hary Susilo (Malahayati Nursing Journal, 2025)
ABSTRACT Breast cancer is a disease that is the first largest cancer case in women in Indonesia. Breast cancer has a very complex impact on cancer sufferers and their families. Caregivers have an obligation and an important role to care for sick families, so social support is really needed to improve the quality of life of caregivers while caring for sick family members. This study aims to analyze the relationship between social support and the quality of life of caregivers in breast cancer patients in Jakarta. This research is a quantitative research with a descriptive correlation design and a cross sectional approach. The data collection method used was distributing questionnaires. The sampling technique in this research used random sampling with 50 respondents. The results of the univariate analysis showed that the majority of caregivers were aged 41-59 years, 31 (62.0%) and the majority of respondents were male, 30 (60.0%). College education level was 25 (50.0%) and the majority of caragiver jobs were private employees as many as 24 (48.0%). The majority of caregivers who have high social support are 35 (70.0%) and the majority of caregivers who have a good quality of life are 46 (92.0%). The results of bivariate analysis using the Spearmen's Rho test with α = 0.05 showed that there was no significant relationship between social support and the quality of life of caregivers of breast cancer patients (p-value = 0.176), the calculated r value was (-193). Keywords: Breast Cancer, Social Support, Quality of Life, Caregiver  ABSTRAK Kanker payudara merupakan penyakit yang menjadi kasus kanker terbesar di Indonesia. Kanker payudara memberikan dampak yang sangat kompleks bagi penderita kanker dan keluarga, Caregiver memiliki kewajiban dan peran penting untuk merawat keluarga yang sakit sehingga dukungan sosial sangat dibutuhkan untuk meningkatkan kualitas hidup caregiver selama merawat anggota keluarga yang sakit. Penelitian ini bertujuan untuk menganalisis hubungan dukungan sosial terhadap kualitas hidup caregiver pasien kanker payudara di Jakarta. Penelitian ini merupakan penelitian kuantitatif dengan desain deskriptif korelasi menggunakan pendekatan cross sectional. Metode pengumpulan data yang digunakan berupa penyebaran kuisioner. Teknik pengambilan sampel dalam penelitian ini menggunakan random sampling dengan responden sebanyak 50 responden. Hasil analisis univariat menunjukan bahwa mayoritas caregiver berusia 41-59 tahun sebanyak 31 (62,0%) dan mayoritas responden berjenis kelamin laki-laki sebanyak 30 (60,0%). Tingkat pendidikan perguruan tinggi sebanyak 25 (50,0%) dan mayoritas pekerjaan karyawan swasta sebanyak 24 (48,0%). Mayoritas caregiver yang memiliki dukungan sosial tinggi sebanyak 35 (70,0%) dan mayoritas cargiver yang memiliki kualitas hidup baik sebanyak 46 (92,0%). Hasil analisis bivariat menggunakan uji Spearmen’s Rho dengan α = 0.05 hasil menunjukkan tidak terdapat hubungan yang signifikan antara dukungan sosial dengan kualitas hidup caregiver pasien kanker payudara (p-value = 0.176), nilai r hitung (-193). Kata Kunci: Kanker Payudara, Dukungan Sosial, Kualitas Hidup, Caregiver